The Implementation of Word Square Media in Increasing the Learning Interest of Ninth Grade Students on the Topic of Digital Economic Development at MTsN 1 Jember - Dini Diah Saputri; Noviana Mariatul Ulfa; Moh. Usman Kurniawan (Majapahit Journal of Islamic Finance and Management, 2025)
This study was conducted to address the low learning interest of ninth-grade students in digital economic development material at MTsN 1 Jember, where traditional lecture-based teaching methods limited engagement and participation. The research aimed to enhance students’ learning interest by applying the Word Square learning medium, which combines educational games with cognitive challenges to promote active and enjoyable learning. Using a qualitative Classroom Action Research (CAR) design following Kemmis and McTaggart’s model, the study was implemented in two cycles involving stages of planning, action, observation, and reflection. Data were collected through observation, interviews, and documentation, focusing on indicators such as attention, participation, and willingness to learn. The findings revealed a significant improvement in students’ learning interest from 49% in the first cycle to 87% in the second indicating that Word Square media effectively fostered enthusiasm, focus, and interaction during lessons. It is concluded that Word Square serves as an effective alternative learning strategy to increase students’ learning interest in digital economic topics and is recommended for broader application across other subjects.